1988
DOI: 10.1148/radiology.169.3.3186989
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arteriovenous malformations: techniques and long-term outcome of embolotherapy.

Abstract: Over a 10-year period, 276 pulmonary arteriovenous malformations (PAVMs) were occluded with balloon embolotherapy in 76 patients, 67 (88%) of whom had hereditary hemorrhagic telangiectasia. Eleven patients (14%) were discovered by means of family screening with measurement of arterial blood gases and chest radiography. Epistaxis, dyspnea, hemoptysis, and hemothorax occurred in 79%, 71%, 13%, and 9% of patients, respectively. Clinical histories of strokes and transient ischemic attacks were present in 18% and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
316
1
15

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(341 citation statements)
references
References 0 publications
9
316
1
15
Order By: Relevance
“…43,44 In a recent study, a higher prevalence of PAVMs was found in females, but only in the HHT1 group, whereas HAVMs were found to be more frequent in females from both HHT1 and 2. 27 Although we did not confirm the influence of sex on the occurrence of PAVMs, we found a strong and significant predominance of HAVMs in females, both for symptomatic and asymptomatic lesions.…”
Section: Discussionmentioning
confidence: 89%
“…43,44 In a recent study, a higher prevalence of PAVMs was found in females, but only in the HHT1 group, whereas HAVMs were found to be more frequent in females from both HHT1 and 2. 27 Although we did not confirm the influence of sex on the occurrence of PAVMs, we found a strong and significant predominance of HAVMs in females, both for symptomatic and asymptomatic lesions.…”
Section: Discussionmentioning
confidence: 89%
“…It is possible that a thrombus may also form in-situ within a PAVM, and this can dislodge and embolize into the cerebral circulation. The radiological literature currently advocates the occlusion of all such malformations having feeding vessels of 3 mm or greater (5).…”
Section: Discussionmentioning
confidence: 99%
“…2) The shunting of air, thrombi, and bacteria passing through pulmonary AVMs, bypassing the filtering capabilities of the lungs, may result in transient ischemic attacks, embolic stroke, or cerebral abscess. 4,6,12) Approximately 20% of patients with HHT will develop pulmonary AVM, and 25-33% of such patients will develop cerebral ischemic symptoms. Brain abscesses will occur in 5-9% of these patients.…”
Section: Discussionmentioning
confidence: 99%